OCCURRENCE OF LIVER HYDATID CYSTS IN A DONKEY AND MOLECULAR CHARACTERIZATION OF ECHINOCOCCUS EQUINUS - Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Simsek, Sami; Gul, Abdurrahman (Allen Press Inc, 2019)
Larval tapeworms of Echinococcus granulosus have been viewed as the etiological agent for the zoonotic disease cystic echinococcosis, but the species is a complex readily divided into several species and genotypes. Cystic echinococcosis is an important public health issue. Here, the case of liver hydatid cyst in a donkey and molecular characterization of the cyst is presented. The fluid-filled hydatid cyst materials were obtained from the liver of a necropsied donkey. Genomic DNA was extracted and PCR amplification of mitochondrial 12S rRNA gene as well as partial sequencing of mitochondrial cytochrome c oxidase subunit 1 (COI) gene were performed. All cysts were fertile. Traditional polymerase chain reaction (PCR) amplification of 12S rRNA and COI yielded bands (254 and 446 base pairs, respectively) for all 3 cyst samples. However, partial COI gene sequences were identical to those reported for Echinococcus equinus (formerly E. granulosus genotype G4). Thus E. equinus is still transmitting among the equids in Turkey but the mitochondrial 12S rRNA gene primers may not be sufficient for the molecular characterization of members of the E. granulosus species/genotype complex. Molecular diagnosis must be confirmed by partial COI sequence analysis.
Keywords: Echinococcus equinus; Donkey; PCR; Turkey